2019
DOI: 10.1002/aic.16879
|View full text |Cite
|
Sign up to set email alerts
|

The encouraging improvement of polyamide nanofiltration membrane by cucurbituril‐based host–guest chemistry

Abstract: The considerable performance enhancement of small molecule‐sieving nanofiltration membrane has been achieved by the functional combination between host–guest chemistry and interfacial polymerization (IP) for the first time in this work. First, the water‐insolubility of cucurbit[6]uril (CB6) was ameliorated by constructing host–guest complex (CB6‐PIP) with piperazine. Second, the incorporation of water‐soluble CB6‐PIP in the selective layer via IP leads to the generation of not only the enlarged conventional po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…In addition to CD, other macrocycle molecules have been investigated to synthesize mixed matrix and thin-film nanocomposite membranes, due to their special characteristics such as pore structure and chemical properties. 136 Using Cucurbit [6]uril (CB6)-piperazine (PIP) pseudorotaxane as the aqueous monomer, CB-containing TFN membranes were then prepared by IP (Fig. 7c).…”
Section: Blendingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to CD, other macrocycle molecules have been investigated to synthesize mixed matrix and thin-film nanocomposite membranes, due to their special characteristics such as pore structure and chemical properties. 136 Using Cucurbit [6]uril (CB6)-piperazine (PIP) pseudorotaxane as the aqueous monomer, CB-containing TFN membranes were then prepared by IP (Fig. 7c).…”
Section: Blendingmentioning
confidence: 99%
“…134 (c) i) The diffusion of i) CB6-PIP in the two phase interface, ii) the sketch of the surface topography of NF-CB-1 membranes, iii) the SEM and AFM images for NF-0.1%CB-1 membrane. 136 Reproduced with permission from Royal Society of Chemistry, Copyright 2015, American Chemical Society, Copyright 2015, and Wiley-VCH, Copyright 2019.…”
Section: Blendingmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Various water treatment technologies have been exploited in the past few decades to produce clean water. 3,4 For example, membrane-based separation techniques such as ultrafiltration, nanofiltration, [5][6][7] reverse osmosis and forward osmosis (FO) [8][9][10] have been implemented at various levels for desalination, wastewater and water treatment. The heart of the successful implementation of these technologies is a high-performance membrane with superior separation efficiency and excellent fouling resistance.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, efforts have been made to fine-tune the surface charge and porosity of PA nanofilms to improve the membrane performance. Specifically, surface coating, [13][14][15] an intermediate layer, 16,17 alternative amine or acid chloride monomers, 3,18,19 additives including surfactants, 12,20 macromolecules, 21,22 and nanoparticles 23,24 have been adopted to successfully achieve a high separation selectivity and high permeation performance. It has been found that a trade-off occurs between water/salt or ion selectivity and pure water permeance.…”
Section: Introductionmentioning
confidence: 99%